Polymer composition with low bending
Patent Information
- Application Number
- KR1020217028010
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-02-20
- Filing Date
- 2020-02-19
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2040-02-19
Smart Images

Figure 112021101144266-PCT00001_ABST
Abstract
Description
Technology Field
[0001] Cross-reference regarding related applications
[0002] This application claims the benefit of priority of U.S. provisional patent application No. 62 / 807,954 filed on February 20, 2019, the entire contents of which are incorporated herein by reference for all purposes.
[0003] The present invention generally relates to a polymer composition comprising a polyolefin polymer and a nucleating agent having an average particle size of less than 2 micrometers (μm). Articles comprising such a composition have low warping. Background Technology
[0004] Polypropylene materials formed by catalysts such as Ziegler-Natta or metallocene compounds are one of the most versatile and commonly used thermoplastic materials for the commercial manufacture of molded plastic products. These materials can be formed into a wide variety of end-use articles, ranging from vehicle parts to food containers, using various plastic molding processes. One of these processes is injection molding.
[0005] In injection molding, plastic parts can be formed from molten polymer resin injected into a mold cavity. The molten resin may be held in the cavity for a sufficient amount of time to allow the part to form. The time required from molding to cooling and removal from the cavity, or the cooling phase, is a critical factor in production time and therefore a critical factor in manufacturing efficiency. Resin properties, such as thermal expansion and compressibility, determine the extent to which the molten resin undergoes dimensional changes during the cooling phase. This dimensional change occurring during the cooling phase is called shrinkage. During the manufacture of plastic parts, shrinkage causes a difference in volume between the original mold and the final molded article. If the dimensional change is uniform, the shrinkage is called isotropic. If the dimensional change is non-uniform or varied, the shrinkage is called anisotropic or differential. Whether isotropic or anisotropic, shrinkage must be accurately considered during the manufacture of plastic parts to obtain a final product with accurate dimensions. Shrinkage rates, especially differential shrinkage rates, can cause warpage or deformation of molded parts.
[0006] Given the discussion above, it would be desirable to develop a method for manufacturing end-use articles from polymer resins with reduced bending. In addition, it would be desirable for such polymer resins to exhibit improved mechanical properties such as impact strength and stiffness. Brief explanation of the drawing
[0007] The advantages of the present invention may become apparent to those skilled in the art by referring to the detailed description that follows and the attached drawings. Figure 1 shows the effect of the average particle size of the nucleating agent of the present invention, which has an average particle size of 0.8 microns, on the bending of a polypropylene polymer compared to a control nucleating agent, which has a particle size in the range of 2 to 4 microns. Figure 2 shows the effect of the average particle size of the nucleating agent of the present invention, which has an average particle size of 0.8 microns, on the shrinkage rate of a polypropylene polymer compared to a control nucleating agent, which has a particle size in the range of 2 to 4 microns. Figure 3 shows the effect of the average particle size of the nucleating agent of the present invention, which has an average particle size of 0.8 microns, on the measured impact (Izod impact) of a polypropylene polymer compared to a control nucleating agent, which has a particle size in the range of 2 to 4 microns. The present invention may allow for various modifications and alternative variations, but specific embodiments thereof are illustrated in the drawings as examples. The drawings may not be proportional. Specific details for implementing the invention
[0008] A discovery has been made that provides a solution to at least some of the problems related to shrinkage when producing injection-molded materials. This solution is based on a composition comprising a polyolefin polymer and a nucleating agent with an average particle size of less than 2 micrometers (μm). The composition of the present invention exhibits more homogeneous isotropic shrinkage characteristics and superior impact characteristics in both longitudinal and transversal directions compared to a composition prepared using nucleating particles with an average particle size exceeding 2 μm. Specifically, when using a nucleating agent of less than 2 μm, the isotropic shrinkage was in the range of 0 to 15%, and the IZOD impact was at least 20 ft·lb / in. Without being bound by theory, it is believed that very small nucleating particles are more uniformly dispersed in the polyolefin polymer, creating more homogeneous spherulites within the polymer matrix. Consequently, due to this uniform "polyolefin crystals cloud" within the polymer matrix, the shrinkage rate is similar in all directions.
[0009] In certain aspects of the present invention, polymer compositions are disclosed. The polymer composition comprises a polyolefin polymer and a nucleating agent having an average particle size of less than 2 μm. The particle size may be measured using a known commercial measuring instrument. For example, the particle size may be measured using a SediGraph® measuring instrument from Micromeritics, USA. The average particle size of the nucleating agent may be in the range of 0.001 μm to 1.9 μm, in the range of 0.6 μm to 1.0 μm, or about 0.8 μm. The composition may contain a nucleating agent in the range of 100 ppm (parts per million) to 20,000 ppm by weight, or about 1,000 ppm. In some examples, the composition may have an isotropic and / or differential shrinkage rate lower than that of a comparable polymer composition comprising the same polyolefin polymer and the same nucleating agent, but having an average particle size of the same nucleating agent greater than or equal to 2 μm. The isotropic shrinkage rate of the composition of the present invention may be less than 80% of that of the control sample. In some embodiments, the isotropic shrinkage rate of the composition of the present invention is in the range of 0% to 15%, or in the range of 0% to 5%, or in the range of 0% to 1%. Compared to a control polymer composition comprising the same polymer and the same nucleating agent, but with an average particle size of the same nucleating agent of 2 μm or more, the Izod impact value of the polymer composition of the present invention (e.g., at least 20 ft·lb / in, or at least 24 ft·lb / in) may be in the range of at least 25%, at least 50%, or 25% to 60%. Izod impact may be measured by ASTM D-256-10. The polyolefin polymer may comprise polypropylene (PP), polyethylene (PE), or both.In some examples, the polyolefin polymer may comprise a homopolymer, a random copolymer, an impact copolymer, or any combination thereof. In some examples, the composition may comprise PP and up to about 5 weight percent of other C2-C8 alpha olefins. In some embodiments, the polyolefin has a melt flow rate of the polyolefin polymer that may be in the range of about 1 g / 10 min to about 200 g / 10 min and / or xylene solubles (XS) that may be in the range of 3.5 to 4.5 weight percent, or a combination thereof. In one example, the composition may be PP having a C2 olefin in the range of 0.5 to 1 weight%, the melt flow rate of the polyolefin polymer may be in the range of about 1 g / 10 min to about 50 g / 10 min, and XS may be 3.5 to 4.5 weight%. In some examples, the polymer composition may include additives (e.g., antioxidant, neutralizing agent, antistatic agents, slip agent, colorant, mold release agent, ultra-violet screening agent, oxidant, UV light absorbent, fire retardant, pigment, dye, filler, flow modifier, or any combination thereof).
[0010] In addition, articles of manufacture comprising the polymer composition of the present invention are disclosed. The articles may be vehicle parts, food containers, hats, computer products, fibers, pipes, films, bottles, non-food containers, cups, lids, plates, trays, and blister packs, artificial grass (pellets, mats, blades, etc.).
[0011] In another aspect of the present invention, a method for manufacturing an article comprising a polymer composition of the present invention is disclosed. The method may include the step of molding the polymer composition. The molding step may include the step of injecting a flowable polymer composition into a mold; the step of solidifying the polymer composition; and the step of releasing the solidified composition from the mold. The volume difference between the flowable polymer composition and the solidified composition may be in the range of 0 to 15%. In some embodiments, the injection molding of the polymer composition into an article may include a cycle time of about 10 seconds or less, or less than 7 seconds.
[0012] In another embodiment, a method for reducing the warping of a polyolefin polymer includes the step of adding a nucleating agent having an average particle size of less than 2 micrometers (μm) to a polyolefin polymer to form a polyolefin composition.
[0013] Other embodiments of the present invention are discussed throughout this application. Any embodiment discussed in relation to one aspect of the present invention is applicable to other aspects of the present invention as well as vice versa. Each embodiment described herein is understood to be an embodiment of the present invention applicable to other aspects of the present invention. Any embodiment discussed herein is intended to be implemented in relation to any method or composition of the present invention, and vice versa. Additionally, the compositions and kits of the present invention may be used to achieve the methods of the present invention.
[0014] The following includes definitions of various terms and phrases used throughout this specification.
[0015] The terms "nucleating agent" or "nucleating particle" refer to compounds that increase the crystallization rate of polymers.
[0016] The term "warpage" refers to a distortion in which the surface of a final product does not follow the intended shape of the design (e.g., mold).
[0017] The term "isotropic shrinkage" refers to uniform shrinkage in all directions, resulting in a final product smaller than intended. The terms "anisotropic shrinkage" or differential shrinkage refer to non-uniform shrinkage in each direction, resulting in warping of the final product. Shrinkage can be calculated by first measuring the length of shrinkage due to cooling in the in-flow direction (referred to as the longitudinal direction when measuring differential shrinkage) and the length of shrinkage occurring in the cross-flow direction (referred to as the transverse direction when measuring differential shrinkage). Multiplying the difference between the in-flow and cross-flow shrinkage by 100% yields the percentage shrinkage. The measurement of shrinkage is limited to measuring changes in the direction of the resin flow and in the direction perpendicular to the direction of the resin flow. Shrinkage can be measured using an optical instrument as disclosed in U.S. Patent No. 7,445,827 or a computerized numerical control (CNC) microscope. An example of a CNC microscope is the QV APEX 302 (Mitutoyo, USA). The polymeric specimen may be a 60 x 60 x 2 mm polymeric specimen formed according to an ISO 294-3 Type D2 mold from the polymeric composition of the present disclosure. Optical measurement of the specimen length is performed by placing the polymeric specimen on a positioning table and setting the positioning table under a microscope camera that communicates with a microprocessor. With the help of specific marks on the display screen of the microprocessor, the positions of both edges of the polymeric specimen are recorded at the beginning and end of a predetermined time period. Subsequently, the length or width of the specimen is inferred from the change in position observed over the predetermined time period.The computational parameters for measuring shrinkage rate are based on ISO 294-3 and ISO 294-1, which have two notable differences: (1) the holding pressure can be selected from 20 MPa, 40 MPa, 60 MPa, or 80 MPa for the same material, and (2) the holding time is kept to a minimum.
[0018] The terms “melt flow rate (MFR)” or “melt index (MI2)” refer to measures of the flowability of a melt of a thermoplastic polymer or blend. In this specification, “melt flow rate” or MFR is used for polypropylene, and “melt index” or “MI2” is used for polyethylene and polyethylene-rich blends. The MFR values mentioned in this specification are values measured according to ASTM D 1238 at a temperature of 230°C with a ram weight of 2.16 kg. The MFR measurements recorded in this specification were performed using an MP1200 melt flow indexer from the American company Tinuius-Olsen. The MI2 values mentioned in this specification are values measured according to ASTM D 1238 at a temperature of 190°C with a ram weight of 2.16 kg. The MI2 measurements recorded in this specification were performed using the MP993 melt flow indexer of the company (Tinuius-Olsen).
[0019] The term "intrinsic viscosity" refers to the ability of a polymer in a solution to increase the viscosity of the solution. Intrinsic viscosity can be measured according to ASTM D-5225-17.
[0020] In this specification, the term "viscosity" is defined as resistance to flow due to internal friction.
[0021] The terms “about” or “approximately” are defined as close as understood by a person skilled in the art. In one non-limiting embodiment, these terms are defined as within 10%, within 5%, within 1%, and / or within 0.5%.
[0022] The terms “weight% (wt.%)”, “vol.%)”, or “mol.%)” refer to the weight percentage, volume percentage, and mole percentage of a component, respectively, based on the total weight containing the component, the total volume of the material, or the total mole. In one non-limiting example, 10 grams of a component in 100 grams of material is 10 weight% of the component.
[0023] The term "substantially" and variations thereof are defined as including a range of within 10%, within 5%, within 1%, or within 0.5%.
[0024] The terms “inhibiting,” “reducing,” “preventing,” or “avoiding,” or any variation thereof, where used in the claims and / or detailed description, include a certain measurable reduction or complete inhibition to achieve a desired result.
[0025] The term "effective" as used in the detailed description and / or claims means appropriate for achieving a desired, expected, or intended result.
[0026] Where used in the claims or detailed description with any of the terms "comprising," "including," "containing," or "having," the use of the words "a" or "an" may mean "one," but is also synonymous with "one or more," "at least one," and "one or more than one."
[0027] The words "including" (and any variation such as "includes"), "having" (and any variation such as "have"), "including" (and any variation such as "includes"), and "containing" (and any variation such as "containing") are inclusive or open-ended and do not exclude additional, unquoted elements or steps of the method.
[0028] The polymer compositions of the present invention may "comprising," "essentially composed of," or "composed of" the specific ingredients, components, and compositions disclosed throughout this specification. In one non-limiting aspect, with respect to the transition phrase "essentially composed of," a fundamental and novel feature of the polymer compositions of the present invention is their ability to be injection molded with uniform and / or reduced shrinkage.
[0029] Other objects, features, and advantages of the present invention will become apparent from the drawings, detailed description, and examples set forth below. However, it should be understood that while these drawings, detailed description, and examples represent specific embodiments of the present invention, they are given merely as examples and are not intended to be limiting. Furthermore, variations and modifications within the spirit and scope of the present invention are considered to be apparent to those skilled in the art from the detailed description thereof. In additional embodiments, features of specific embodiments may be combined with features of other embodiments. For example, features of one embodiment may be combined with features of any of the other embodiments. In additional embodiments, additional features may be added to the specific embodiments disclosed herein.
[0030] A discovery has been made that provides a solution to at least some of the problems associated with the injection molding of polymer compositions. This discovery is based on the use of a nucleating agent with an average particle size of less than 2 μm. The resulting polymer composition and the manufactured articles produced therefrom are less warped and possess improved toughness. Without being bound by theory, it is believed that the uniform dispersion of polymer crystals (e.g., PP crystals) within the polymer matrix can act as a physical barrier against growing cracks. Better dispersion can prevent any "weak spots," and lower warping can lead to lower "tension" within the matrix, which can result in better impact properties for the molded articles. Additionally, the use of smaller nucleating agents (less than 2 μm) can result in a uniform shrinkage rate in all directions, even if shrinkage occurs at all. In addition, a uniform shrinkage rate can result in lower warping of the injection-molded article upon cooling without significantly affecting other mechanical and optical properties.
[0031] These and other non-limiting aspects of the present invention are discussed in more detail in the following sections.
[0032] A. Materials
[0033] The polymer composition may include a polyolefin polymer, a nucleating agent having an average particle size of 2 μm, and optional additives.
[0034] 1. Polyolefin polymer
[0035] Polyolefin polymers may be thermoplastic polymers. The polymers may be homopolymers, random copolymers, impact copolymers, or any combination thereof. Non-limiting examples of polyolefins include polypropylene and polyethylene. Polyolefins may be produced by any polymerization process (e.g., high pressure process, slurry process, solution process and / or gas phase process) using any known polymer polymerization catalyst (e.g., Ziegler-Natta catalyst, chromium or Phillips catalyst, single site catalyst, metallocene catalyst, etc.). Polyethylene may comprise a homopolymer of ethylene or a copolymer of ethylene and at least one alpha-olefin (e.g., butene, hexene, octene, etc.). Non-limiting examples of polyethylene include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene copolymers, or blends thereof. Polypropylene includes homopolymers of propylene, copolymers of propylene and other olefins, and terpolymers of propylene, ethylene, and diene. Controlled rheology grade polypropylene (CRPP) is a polypropylene polymer that has been further processed (e.g., via a cracking process) to produce a polypropylene polymer having a target higher melt flow index (MFI), lower molecular weight, and / or a narrower molecular weight distribution than the starting polypropylene. Reactor grade, also known as low-order polypropylene, may be used.In addition, polyolefins can be produced using any other method, such as a combination of a Ziegler-Natta catalyst and a metallocene catalyst, as disclosed in, for example, patent literature (U.S. Patent Nos. 7,056,991 and 6,653,254). The polyolefin polymer may have a melt flow rate in the range of 1.0 g / 10 min to 200 g / 10 min, or 0.1 g / 10 min, 0.5 g / 10 min, 1 g / 10 min, 10 g / 10 min, 20 g / 10 min, 30 g / 10 min, 40 g / 10 min, 50 g / 10 min, 60 g / 10 min, 70 g / 10 min, 80 g / 10 min, 90 g / 10 min, 100 g / 10 min, 110 g / 10 min, 120 g / 10 min, 130 g / 10 min, 140 g / 10 min, 150 g / 10 min, 160 g / 10 min, 170 g / 10 min, 180 g / 10 min, 190 g / 10 min and The polyolefin polymer may have at least one melt flow rate of 200 g / 10 min, may be equivalent to at least one of these melt flow rates, or may have a melt flow rate between any one of these. The polyolefin polymer may have an XS in the range of 3.5 to 4.5 weight%, or may have at least one XS of 3.5, 3.6, 3.7, 3.8, 3.9, 4, 4.1, 4.2, 4.3, 4.4, 4.5 weight%, may be equivalent to at least one of these XS, or may have an XS between any two of these. Polyolefin homopolymers (e.g., PP homopolymers) may contain other alpha olefins in the range of 0% to about 5% (e.g., 0, 1, 2, 3, 4, 5% by weight and any value or range between these), including but not limited to C2-C8 alpha olefins such as ethylene, 1-butene, and 1-hexene. The homopolymers may be manufactured or obtained from commercial sources such as a French company (TOTAL Petrochemicals) and / or a US company (Total Petrochemicals USA, Inc.).Non-limiting examples of homopolymers and copolymers include TOTAL polypropylene 3620WZ and TOTAL polypropylene 3727WZ.
[0036] In some embodiments, the polyolefin polymer is a polypropylene impact copolymer (Ppic). The copolymer phase of PPic may be a random copolymer of propylene and ethylene, also referred to as ethylene / propylene rubber (EPR). Without being bound by theory, the EPR portion of PPic has rubber-like properties that, when incorporated into the matrix of the homopolymer component, can function to provide increased impact strength to PPic. In one embodiment, the EPR portion of PPic comprises more than about 14% by weight of PPic, alternatively more than about 18% by weight of PPic, or alternatively a range of about 14% to about 18% by weight of PPic. The amount of ethylene present in the EPR portion of PPic may be in the range of about 38% to about 50% based on the total weight of the EPR portion, or alternatively a range of about 40% to about 45%. The amount of ethylene present in the EPR portion of PPic can be measured spectrophotometrically using Fourier transform infrared spectroscopy (FTIR). Specifically, FTIR spectra of the polymer samples are recorded for a series of samples having known ERP ethylene content. For each ethylene concentration, 720 cm⁻¹ is used. -1 / 900 cm -1The transmittance ratio at can be calculated, and a calibration curve is obtained. Linear regression analysis is performed on the calibration curve to derive a formula used to determine the EPR ethylene content of the sample material. The EPR portion of PPic may exhibit an intrinsic viscosity different from the intrinsic viscosity of the propylene homopolymer component. In one embodiment, the intrinsic viscosity of the EPR portion of PPic may be greater than about 2.0 dl / g, alternatively in the range of about 2.0 dl / g to about 3.0 dl / g, alternatively in the range of about 2.4 dl / g to about 3.0 dl / g, alternatively in the range of about 2.4 dl / g to about 2.7 dl / g, or alternatively in the range of about 2.6 dl / g to about 2.8 dl / g. In one embodiment, the melt flow rate (MFR) of PPic may be in the range of about 65 g / 10 min to about 130 g / 10 min, alternatively in the range of about 70 g / 10 min to about 120 g / 10 min, alternatively in the range of about 70 g / 10 min to about 100 g / 10 min, alternatively in the range of about 70 g / 10 min to about 90 g / 10 min, alternatively in the range of about 75 g / 10 min to about 85 g / 10 min, or alternatively in the range of about 90 g / 10 min. Excellent flow characteristics, indicated by a high MFR, allow for the production of molded polymer parts at a high throughput. In one embodiment, PPic is an unmodified reactor-grade resin. In some embodiments, PPic is a controlled rheological-grade resin. PPic and other impact copolymers may be obtained from commercial sources or manufactured. Representative examples of suitable PPic include, but are not limited to, TOTAL polypropylene 4920W and TOTAL polypropylene 4920WZ, impact copolymer resins available from the company (Total Petrochemicals USA Inc.).
[0037] Ziegler-Natta Catalysts
[0038] Typically, the catalyst system used in a bulk loop reactor for the commercial production of polyolefin (e.g., polypropylene or polyethylene) homopolymers and / or copolymers (polymer production in the range of 1 to 5 tons / hour over a period of at least 5 days to at least 2 years, and preferably in the range of at least 1 ton to at least 50 tons / hour) is generally known as a conventional Ziegler-Natta catalyst system (hereinafter also referred to as "Ziegler-Natta catalyst" or "Ziegler-Natta catalyst system"). Non-limiting examples of conventional Ziegler-Natta catalysts are disclosed in patent documents (U.S. Patent No. 4,701,432; U.S. Patent No. 4,987,200; U.S. Patent Nos. 3,687,920; 4,086,408; 4,376,191; 5,019,633; 4,482,687; 4,101,445; 4,560,671; 4,719,193; 4,755,495; and 5,070,055), the entire contents of which are respectively incorporated herein by reference. Such Ziegler-Natta catalyst systems may comprise a Ziegler-Natta catalyst, a support, one or more internal donors, and one or more external donors.
[0039] Conventional Ziegler-Natta catalysts are stereospecific complexes formed from transition metal halides and metal alkyls or hydrides, and can produce isotactic polypropylene. Ziegler-Natta catalysts are derived from transition metal halides, such as titanium, chromium, or vanadium, containing metal hydrides and / or metal alkyls, and generally from organoaluminum compounds as co-catalysts. The catalyst may comprise titanium halides supported on magnesium compounds. For example, Ziegler-Natta catalysts such as titanium tetrachloride (TiCl4) supported on active magnesium dihalides, such as magnesium dichloride or magnesium dibromide, as disclosed in the patent literature of Mayr et al. (U.S. Patent Nos. 4,298,718 and 4,544,717), are supported catalysts. Silica may also be used as a support. Supported catalysts may be used with co-catalysts such as alkylaluminum compounds, for example, triethylaluminum (TEAL), trimethylaluminum (TMA), and triisobutylaluminum (TIBAL).
[0040] Conventional Ziegler-Natta catalysts can be used with one or more internal electron donors. These internal electron donors may be added during the preparation of the catalyst and may be bound to a support or complexed to a transition metal halide. Suitable Ziegler-Natta catalysts containing diether-based internal donor compounds are available as Mitsui RK-100 and Mitsui RH-220 manufactured by Mitsui Chemicals, Inc. The RK-100 catalyst additionally contains an internal phthalate donor. The Ziegler-Natta catalyst may be a supported catalyst. Suitable support materials include magnesium compounds such as magnesium halides, dialkoxymagnesium, alkoxymagnesium halides, magnesium oxyhalides, dialkylmagnesium, magnesium oxide, magnesium hydroxide, and magnesium carboxylates. Typical magnesium levels range from about 12% to about 20% based on the weight of the catalyst. The RK-100 catalyst contains about 2.3 wt% titanium and about 17.3 wt% magnesium. The RK-220 catalyst contains about 3.4 wt% titanium and about 14.5 wt% magnesium.
[0041] Conventional Ziegler-Natta catalysts can also be used with one or more external donors. Generally, these external donors function as stereoselective control agents to regulate the amount of atactic or non-stereoregular polymers produced during the reaction, thereby reducing the amount of xylene solubles. Examples of external donors include organosilicon compounds such as cyclohexylmethyl dimethoxysilane (CMDS), dicyclopentyl dimethoxysilane (CPDS), and diisopropyl dimethoxysilane (DIDS). However, external donors can reduce catalytic activity and may tend to reduce the melt flow of the produced polymer.
[0042] Metallocene Catalyst System
[0043] Another catalyst system useful for polymerizing polyolefins (e.g., PP and PE) is based on metallocenes. Metallocenes can generally be characterized as coordination compounds comprising one or more cyclopentadienyl (Cp) groups (which may or may not be substituted and may be identical or different) coordinated to a transition metal via an n-bond. The Cp groups can also form other continuous ring structures, including, for example, indenyl, azulenyl, and fluorenyl groups, by substitution with linear, branched, or cyclic hydrocarbyl radicals, and preferably by cyclic hydrocarbyl radicals. These additional ring structures may also be or may not be substituted by hydrocarbyl radicals, and preferably C1 to C20 hydrocarbyl radicals. Metallocene compounds may be combined with an activator and / or co-catalyst (described in more detail below), or with a reaction product of an activator and / or co-catalyst such as methylaluminoxane (MAO), for example, and optionally with an alkylation / scavenging agent such as a trialkylaluminum compound (TEAL, TMA and / or TIBAL). Various types of metallocenes that can be supported are known in the industry. Typical carriers may be any carriers such as talc, inorganic oxides, clay and clay minerals, ion-exchanged layered compounds, diatomite, silicates, zeolites, or resin carrier materials such as polyolefins.Certain inorganic oxides include silica and alumina, which are used alone or in combination with other inorganic oxides such as magnesia, titania, and zirconia. Non-metallocene transition metal compounds, such as titanium tetrachloride, are also included in the supported catalyst components. The inorganic oxide used as a support is characterized by having an average particle size in the range of 30 to 600 microns, preferably in the range of 30 to 100 microns, a surface area in the range of 50 to 1,000 square meters per gram, preferably in the range of 100 to 400 square meters per gram, and a pore volume in the range of 0.5 to 3.5 cc / g, preferably in the range of about 0.5 to 2 cc / g.
[0044] Any metallocene may be used in the practice of the present invention. Unless otherwise specified, as used herein, "metallocene" comprises a single metallocene composition or two or more metallocene compositions. Metallocenes are generally formulated ([L] m M[A] n It is a bulky ligand transition metal compound represented as ), where L is a bulky ligand, A is a leaving group, and M is a transition metal, and m and nThe total ligand valence corresponds to the transition metal valence. The ligands (L and A) can be bridged to each other, and if two ligands (L and / or A) are present, they can be bridged. The metallocene compound may be a full-sandwich compound having two or more ligands (L) that may be cyclopentadienyl ligands or cyclopentadiene-derived ligands, or a half-sandwich compound having one ligand (L) that is a cyclopentadienyl ligand or cyclopentadienyl-derived ligand. The transition metal atom may be a transition metal of Group 4, Group 5, or Group 6 of the periodic table and / or a metal of the lanthanide series and actinide series. Non-limiting examples of metals include zirconium, titanium, and hafnium. Other ligands, such as leaving groups, may be bound to transition metals. Non-limiting examples of ligands include hydrocarbyl, hydrogen, or any other monovalent anionic ligand. For example, a cross-linked metallocene is of the general formula (RCpCp'MeQ x It can be explained as follows. Me represents a transition metal element, Cp and Cp' represent cyclopentadienyl groups that are identical or different and may or may not be substituted, respectively, and Q is an alkyl or other hydrocarbyl or halogen group, and xis a number that may be in the range of 1 to 3, and R is a structural bridge extending between cyclopentadienyl rings. Metallocene catalysts and metallocene catalyst systems for producing isotactic polyolefins are disclosed in patent documents (U.S. Patent Nos. 4,794,096 and 4,975,403) incorporated herein by reference. These patent documents disclose chiral, stereorigid metallocene catalysts that polymerize olefins to form isotactic polymers and are particularly useful for the polymerization of highly isotactic polypropylene.
[0045] Suitable metallocene catalysts are, for example, patent documents (U.S. Patent Nos. 4,530,914; 4,542,199; 4,769,910; 4,808,561; 4,871,705; 4,933,403; 4,937,299; 5,017,714; 5,026,798; 5,057,475; 5,120,867; 5,132,381; 5,155,180; 5,198,401; 5,278,119; 5,304,614; 5,324,800; 5,350,723; 5,391,790; 5,436,305; 5,510,502; 5,145,819; 5,243,001; 5,239,022; 5,329,033; 5,296,434; 5,276,208; 5,672,668; 5,304,614, 5,374,752; 5,510,502; 4,931,417; 5,532,396; 5,543,373; 6,100,214; 6,228,795; 6,124,230; 6,114,479; 6,117,955; 6,087,291; 6,140,432; 6,245,706; 6,194,341, 6,399,723, 6,380,334, 6,380,331, 6,380,330, 6,380,124, 6,380,123, 6,380,122, 6,380,121, 6,380,120, 6,376,627, 6,376,413, 6,376,412, 6,376,411, 6,376,410, 6,376,409, 6,376,408, 6,376,407, 5,635,437, 5,554,704, 6,218,558, 6,252,097, 6,255,515 and European publications No. 549 900; 576 970; 611 773; and WO 97 / 32906; 98 / 014585; 98 / 22486; and 00 / 12565) are disclosed. Examples of catalysts suitable for the production of PPic are disclosed in patent literature (U.S. patents No. 4,107,413; 4,294,721; 4,439,540; 4,114,319; 4,220,554; 4,460,701; 4,562,173; and 5,066,738).
[0046] Metallocenes can be used in combination with any form of activator to create an active catalytic system. In this specification, the term “activator” is defined as any compound or component, or a combination of compounds or components, capable of enhancing the ability of one or more metallocenes to polymerize olefins into polyolefins. Alklyalumoxanes, such as methylalumoxane (MAO), are commonly used as metallocene activators. Typical alkylalumoxanes contain repeating units ranging from about 5 to 40. Alumoxane solutions, particularly methylalumoxane solutions, can be obtained from commercial sources as solutions of various concentrations. There are various methods for manufacturing alumoxane, and non-limiting examples thereof are disclosed in patent documents (U.S. Patent Nos. 4,665,208, 4,952,540, 5,091,352, 5,206,199, 5,204,419, 4,874,734, 4,924,018, 4,908,463, 4,968,827, 5,308,815, 5,329,032, 5,248,801, 5,235,081, 5,103,031 and EP-A-0 561 476, EP 0 279 586, EP-A-0 594 218 and WO 94 / 10180), the entire contents of which are incorporated herein by reference.
[0047] Ionizing activators can also be used to activate metallocenes. Such activators are neutral or ionic, or compounds such as tri(n-butyl)ammonium tetrakis(pentafluorophenyl)borate that ionize neutral metallocene compounds. These ionizing compounds may contain active protons, or may contain some other cations that are bonded to the residual ion of the ionizing compound but are not coordinated or are loosely coordinated. Combinations of activators may also be used; for example, a combination of alumoxane and an ionizing activator can be found in patent literature (WO 94 / 07928).
[0048] Descriptions of ionic catalysts for coordination polymerization composed of metallocene cations activated by non-coordinating anions are provided in early studies of patent documents (EP-A-0 277 003, EP-A-0 277 004 and U.S. Patent No. 5,198,401 and WO-A-92 / 00333), the full contents of which are incorporated herein by reference. These teach a preferred method for preparation in which metallocenes (bisCp and monoCp) are protonated by an anionic precursor so that alkyl / hydride groups are extracted from the transition metal to achieve both charge balance and cationicity by non-coordinating anions. Suitable ionic salts include aluminum salts or tetrakis-substituted borates having fluorided aryl-constituents such as phenyl, biphenyl, and naphthyl.
[0049] The term "noncoordinating anion (NCA)" refers to an anion that is not coordinated to a cation or is weakly coordinated to a cation and remains unstable enough to be substituted by a neutral Lewis base. A "compatible" noncoordinating anion is an anion that does not degrade to neutral when the initially formed complex is decomposed. Additionally, this anion will not transfer anionic substituents or fragments to the cation to allow for the formation of neutral tetracoordinating metallocene compounds and neutral byproducts from the anion.
[0050] The use of ionizing ionic compounds that do not contain active protons but can produce both active metallocene cations and non-coordinating anions is also known. For example, refer to patent documents (EP-A-0 426 637 and EP-A-0 573 403), the full contents of which are incorporated herein by reference. An additional method for preparing ionic catalysts involves ionizing anion precursors, such as tris(pentafluorophenyl) borane, which are initially neutral Lewis acids but form cations and anions through an ionization reaction with a metallocene compound; for example, refer to patent document (EP-A-0 520 732), the full contents of which are incorporated herein by reference. An ionic catalyst for further polymerization can also be prepared by the oxidation of metal centers of a transition metal compound by an anionic precursor containing metallic oxidizing groups along with anionic groups, and refer to patent document (EP-A-0 495 375), the entire contents of which are incorporated herein by reference.
[0051] If the metal ligand contains halogen moieties (e.g., bis-cyclopentadienyl zirconium dichloride) that cannot undergo ionizing abstraction under standard conditions, these may be converted through known alkylation reactions with lithium or aluminum hydrides or organometallic compounds such as alkyl, alkylalumoxane, Grignard reagents, etc. Refer to patent literature (EP-A-0 500 944 and EP-A1-0 570 982) regarding in situ processes describing the reaction of alkyl aluminum compounds with dihalo-substituted metallocene compounds prior to or with the addition of an activating anionic compound.
[0052] Preferred methods for supporting an ionic catalyst comprising a metallocene cation and NCA are disclosed in patent documents (U.S. Patent Nos. 5,643,847; 6,228,795; and 6,143,686), the full contents of which are incorporated herein by reference. Where a carrier composition is used, such an NCA carrier method may involve using neutral anion precursors that are Lewis acids strong enough to react with hydroxyl reactive functionalities present on the silica surface to form covalent bonds with Lewis acids. Additionally, when the activator for the metallocene supported catalyst composition is NCA, preferably NCA is added to the carrier composition first, followed by the addition of the metallocene catalyst. When the activator is MAO, preferably MAO and the metallocene catalyst are dissolved together in a solution. Subsequently, the carrier is brought into contact with the MAO / metallocene catalyst solution. Other methods and order of addition will be apparent to those skilled in the art.
[0053] Polyolefin Production
[0054] Polyolefins can be formed by placing one or more olefin monomers (e.g., ethylene, propylene) alone or together with other monomers in a suitable reaction vessel in the presence of a catalyst (e.g., Ziegler-Natta, metallocene, etc.) and under suitable reaction conditions for polymerization. Any suitable equipment and process for polymerizing the olefins into polymers may be used. For example, such processes may include liquid phase, gas phase, slurry phase, bulk phase, high-pressure processes, or combinations thereof. These processes are disclosed in detail in patent documents (U.S. Patent Nos. 5,525,678; 6,420,580; 6,380,328; 6,359,072; 6,346,586; 6,340,730; 6,339,134; 6,300,436; 6,274,684; 6,271,323; 6,248,845; 6,245,868; 6,245,705; 6,242,545; 6,211,105; 6,207,606; 6,180,735; and 6,147,173), the entire contents of which are incorporated herein by reference.
[0055] Polyolefins can be formed by a gas-phase polymerization process. An example of a gas-phase polymerization process includes a continuous cycle system in which a cycling gas stream (also known as a recirculation stream or fluidization medium) is heated within a reactor by the heat of polymerization. Heat is removed from the cycling gas stream at other parts of the cycle by a cooling system outside the reactor. A cycling gas stream containing one or more monomers can be continuously circulated through a fluidized bed in the presence of a catalyst under reactive conditions. The cycling gas stream is typically recovered from the fluidized bed and recirculated back into the reactor. At the same time, the polymer product can be recovered from the reactor, and fresh monomers can be added to replace the polymerized monomers. The reactor pressure in the gas-phase process can vary from 100 psig to 500 psig, or from 200 psig to 400 psig, or from 250 psig to 350 psig. The reactor temperature in the gas phase process may be in the range of 30°C to 120°C, or in the range of 60°C to 115°C, or in the range of 70°C to 110°C, or in the range of 70°C to 95°C. Non-limiting examples of polymerization processes are disclosed in patent documents (U.S. Patent Nos. 4,543,399; 4,588,790; 5,028,670; 5,317,036; 5,352,749; 5,405,922; 5,436,304; 5,456,471; 5,462,999; 5,616,661; 5,627,242; 5,665,818; 5,677,375; and 5,668,228), the entire contents of which are incorporated herein by reference.
[0056] PPic can be formed by a sequential polymerization process. The polymerization reaction can be carried out in a two-reactor configuration in which a catalyst, typically a Ziegler-Natta catalyst, and propylene are charged into a first loop reactor equipped with a circulation pump. Within the reactor, a propylene homopolymer is formed on the surface of catalyst particles. Subsequently, the propylene polymer-coated catalyst particles are transferred to one or more secondary gas-phase reactors with fluidized beds, where a copolymer is produced by the copolymerization of propylene and ethylene in the presence of a catalyst, typically the aforementioned Ziegler-Natta catalyst. Standard equipment and procedures for polymerizing propylene and other alpha-olefins, such as ethylene, into impact copolymers are known to those skilled in the art.
[0057] 2. Nucleating Agent
[0058] The polymer composition of the present invention also comprises a nucleating agent with an average particle size of less than 2 microns, or a combination of nucleating agents. The nucleating agent may function to improve the optical properties of the resin, improve the processing productivity of the resin by speeding cycles, and / or improve mechanical properties such as stiffness and heat resistance. For example, during the crystallization of a polymer such as polypropylene, the formed crystals may generally be larger than the wavelength of light. Crystals of this size can refract light, thereby reducing the clarity of the copolymer. Without being bound by theory, the nucleating agent may act as a crystallization site and provide a non-uniform surface that increases the crystallization rate of the polymer. In the presence of the nucleating agent, crystals may be formed at higher temperatures, and a higher crystal formation rate may lead to the formation of smaller crystals, such as spheroids. The smaller crystal size allows light to pass through with a reduced refractive index, thereby increasing the clarity of the polymer. In one embodiment, any nucleating agent that is chemically compatible with the polymer resin and capable of reducing its isotropic and / or differential shrinkage rates may be included in the composition in an amount effective for imparting desired physical properties. As illustrated in the examples in a non-limiting manner, a nucleating agent having an average particle size of less than 2 microns may provide reduced warping, reduced and / or uniform shrinkage, and / or impact properties compared to materials containing larger nucleating agents. The isotropic shrinkage rate may be improved by at least 80%. In some embodiments, warping was not observed at all or was observed minimally. As previously mentioned, it is believed that very small nucleating particles are more uniformly dispersed in the polyolefin polymer, creating a more homogeneous cloud within the polymer matrix. Consequently, due to the uniform "polyolefin crystal cloud" within the polymer matrix, the shrinkage rate is similar in all directions.The uniform dispersion of PP crystals within the polymer matrix is believed to act as a physical barrier against growing cracks. In some embodiments, the average particle size of the nucleating agent is in the range of 0.001 to 1.9 microns (μm), or in the range of 0.6 to 1 micron, or any one of 0.001, 0.005, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.5, and 1.9 microns, or is equivalent to any one of these, or is between any two of these.
[0059] In one embodiment, the nucleating agent is ultrafine talc, a carboxylic acid or a salt thereof, an organophosphate, pine rosin, or a sorbitol compound, or any combination thereof. Non-limiting examples of carboxylic acids or salts thereof include benzoates, metal benzonates, sodium benzonates, lithium benzonates, norbornane carboxylic acids or salts thereof, or any combination thereof. In one embodiment, the nucleating agent is ultrafine talc. The nucleating agent is in the range of 100 ppm to about 20,000 ppm, in the range of about 500 ppm to about 10,000 ppm, in the range of about 1,000 ppm to about 5,000 ppm, or 100, 500, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 11000, 12000, 13000, 14000, 15000, 16000, 1700, 1800, It may be present in an amount of either 1,900 and 20,000 ppm, or an amount equivalent to either of these, or an amount between any two of these. The nucleating agent may be obtained from commercial sources or manufactured through chemical processes. A commercial source of ultrafine talc is MicroTuff® AGD 609 by the U.S. company Mineral Technologies Inc.
[0060] 3. Optional Additives
[0061] The polymer composition of the present invention may further include at least one additive. Non-limiting examples of additives include anti-blocking agents, antistatic agents, antioxidants, neutralizing agents, blowing agents, crystallization aids, dyes, flame retardants, fillers, impact modifiers, release agents, oils, other polymers, pigments, processing agents, reinforcing agents, nucleating agents, clarifying agents, slip agents, flow modifiers, stabilizers, UV blockers, and combinations thereof. Additives may be available from various commercial suppliers. Non-limiting examples of commercial additive suppliers include the German company BASF, the American company Dover Chemical Corporation, the Dutch company AkzoNobel, the American company Sigma-Aldrich®, and the company Atofina Chemicals, Inc.
[0062] In one embodiment, the polymer composition may include a release agent and an antistatic agent. The release agent and the antistatic agent may each be a combination of a metallic sterate and a glycerol ester. In one embodiment, the release agent and the antistatic agent may be used as a combination or individually. In some embodiments, the release agent and the antistatic agent are the same compound. Non-limiting examples of suitable glycerol esters include glycerol monosterate (GMS) present iteratively in an amount of about 500 ppm to about 5000 ppm, alternatively about 750 ppm to about 3000 ppm, alternatively about 1000 ppm to about 2000 ppm, alternatively about 1000 ppm to about 1500 ppm, or alternatively about 1250 ppm. Without being bound by theory, an antistatic agent, such as GMS, can function by migrating to the surface of a polymer material and forming a film of water that dissipates static electricity present on the surface of the material. An antistatic agent present in the disclosed amount can be effective in reducing static electricity without adversely affecting the adhesion of additional components or materials, such as paints, to end-use articles made from the disclosed polymer composition.
[0063] Non-limiting examples of suitable release agents are metal stearates, such as zinc stearate, which are present in amounts ranging from about 500 ppm to about 5000 ppm, alternatively from about 500 ppm to about 3000 ppm, alternatively from about 750 ppm to about 2000 ppm, alternatively from about 750 ppm to about 1500 ppm, and alternatively from about 1000 ppm. Alternatively, the release agent is N,N' distearoylethylenediamine, which is present in amounts ranging from about 250 ppm to about 2500 ppm, alternatively from about 500 ppm to about 2000 ppm, alternatively from about 750 ppm to about 1500 ppm, and alternatively from about 1000 ppm. Without being bound by theory, release agents can be used to reduce the degree of adhesion of the final molded part to the mold cavity. Release agents can be used to reduce the degree of adhesion of the final molded part to the mold cavity.
[0064] In one embodiment, the polymer composition may include an acid neutralizer. In some embodiments, the acid neutralizer may be hydrotalcite present in an amount of about 100 ppm to about 1000 ppm, alternatively about 150 ppm to about 400 ppm, or alternatively about 300 ppm. In some embodiments, the release agent and the acid neutralizer comprise a single compound. Non-limiting examples of a suitable combined release agent and acid neutralizer may include calcium stearate present in an amount of about 200 ppm to about 2000 ppm, alternatively about 200 ppm to about 1500 ppm, alternatively about 350 ppm to about 1000 ppm, alternatively about 350 ppm to about 750 ppm, or alternatively about 500 ppm. Acid neutralizing agents can function to remove residues remaining in the polymer resin from the polymerization catalyst and prevent corrosion of the mold cavity.
[0065] B. Preparation of Polymer Compositions
[0066] The preparation of the polymer composition may be carried out in a conventional mixing machine in which the polyolefin and the nucleating agent or a combination of nucleating agents can be melted and mixed with optional additives. Suitable machines are known to those skilled in the art. Non-limiting examples include mixers, kneaders, and extruders. In certain aspects, the process may be carried out in an extruder by introducing additives during the process. Non-limiting examples of extruders may include single-screw extruders, reverse and co-rotating twin-screw extruders, planetary-gear extruders, ring extruders, or co-kneaders. Additionally, the polyolefin and the nucleating agent may also be dry-blended, and the resulting polymer blend is used in general polymer processes (e.g., blown film extrusion, foam extrusion, sheet extrusion-thermoforming, etc.). In some embodiments, the nucleating agent may be obtained and mixed with polypropylene and / or one or more optional additives to produce the polymer blend of the present invention. The polyolefin, the nucleating agent, or the blend thereof may be exposed to a high temperature for a sufficient amount of time during blending. The blending temperature may be higher than the softening point of the polymer. This "melt mixing" or "melt compounding" helps to uniformly disperse the nucleating agent in the polyolefin polymer matrix.
[0067] Additives may be added individually to the polymer composition or pre-mixed. For example, the additives of the present invention may be pre-mixed so that a blend is formed before being added to a blend of polyolefin and a nucleating agent. The additive containing the blend may be exposed to a high temperature for a sufficient amount of time during the incorporation and / or blending of the additive. The incorporation of the additive into the polyolefin resin may be carried out, for example, by mixing the aforementioned components using conventional methods in process technology. The blending temperature may be higher than the softening point of the polymer. In certain aspects, the process may be carried out at a temperature in the range of about 160°C to 280°C. Such "melt mixing" or "melt synthesis" results in a uniform dispersion of the additives in the polyolefin polymer matrix.
[0068] C. Polymer Compositions
[0069] The polymer composition may comprise a polyolefin polymer and a nucleating agent having an average particle size of less than 2 microns in the aforementioned amounts. The nucleating agent may be a combination of different nucleating agents, and the overall average particle size of the combination of nucleating agents may be less than 2 microns. In some embodiments, the polymer blend may comprise a nucleating agent in the range of 100 ppm to about 20,000 ppm, in the range of about 500 ppm to about 10,000 ppm, and in the range of about 1,000 ppm to about 5,000 ppm, and the remainder is a polyolefin and optional additives.
[0070] Polymer compositions may exhibit enhanced mechanical properties, such as increased impact strength reflected in increased Izod impact strength and / or increased stiffness reflected in an increased flexural modulus, and / or reduced shrinkage and / or reduced bending, such as isotropic shrinkage. Izod impact is defined as the kinetic energy required to cause a fracture in a specimen and sustain the crack until the sample breaks. The Izod impact strength test measures the resistance of a polymer sample to fracture due to flexural impact, as indicated by the energy consumed by a pendulum-type hammer when fracturing a standard specimen with a single strike. The specimen is notched to concentrate stress and promote brittleness rather than ductile fracture. Specifically, the Izod impact test measures the amount of energy lost by the pendulum during the fracture of the specimen. The energy lost by the pendulum is the sum of the energy required to initiate sample rupture and propagate the rupture across the specimen, and other energy losses associated with the measurement system (e.g., friction of the pendulum bearing, vibration of the pendulum arm, and sample toss energy). The polymer composition of the present invention may have an increased Izod impact value of at least 25%, 30%, at least 40%, at least 60%, or a range of 25% to 60%, or any value or range between these, compared to a control polymer composition comprising the same polymer and the same nucleating agent, but wherein the average particle size of the same nucleating agent is 2 μm or greater. For example, the composition of the present invention may have an Izod impact strength of 20 ft·lb / in, or at least 24 ft·lb / in, whereas a composition comprising a larger-sized nucleating agent has an Izod impact strength of less than 16 ft·lb / in.
[0071] In one exemplary embodiment, the polymer compositions described herein and the end-use articles formed therefrom exhibit an isotropic shrinkage rate of less than 20%, less than 10%, less than 5%, or no shrinkage at all. The isotropic shrinkage rate of the composition may be in the range of 0% to 15%, or in the range of 0% to 5%, or in the range of 0% to 1%. The polymer composition may have a lower isotropic shrinkage rate than a polymer blend having a nucleating agent having an average particle size greater than 2 microns (e.g., talc with an average particle size in the range of 2 to 6 mm). For example, the isotropic shrinkage rate of the composition of the invention may be less than 80%, less than 90%, or less than 95% of the reference sample.
[0072] D. Articles of Manufacture
[0073] The polymer blend composition is generally collected as pellets that can be stored for a predetermined period of time or immediately available for use in a molding process. The molding process may include injection molding, blown film, extrusion coating, extrusion blow molding, injection stretch blow molding, thermoforming, profile extrusion, compression molding, or sheet extrusion. The final molded product is, for example, a molded part, sheet, film, fiber, etc. Examples of molded parts include vehicle parts, food containers, caps, computer products, fibers, pipes, films, bottles, non-food containers, cups, lids, plates, trays, and blister packs and artificial grass. Artificial grass may comprise at least one of pellets, mats, and blades.
[0074] In one embodiment, the plastic molding process may include injection molding. In injection molding, a polymer resin is supplied to an injection molding machine through a hopper. The resin enters the injection barrel by gravity through a feed section and is heated to an appropriate melting temperature. Subsequently, the molten resin is injected into a mold cavity and molded into a desired part. The mold is continuously cooled to a temperature at which the resin solidifies and becomes cold to the touch. While filling the cavity, the molten resin flows in the direction of injection called the inflow flow and spreads out perpendicular to the injection flow in a direction called the cross flow. In one embodiment, the polymer composition may be used to form a final product in a part weight of less than about 65 grams, alternatively in the range of about 52 grams to about 55 grams, or less than any one of 65, 64, 63, 62, 61, 60, 59, 58, 57, 56, 55 grams, or equivalent to any one of these, or between any two of these. These articles may be formed using a suitable injection molding machine operation in a cycle time in the range of about 10 seconds or less, alternatively 7.0 seconds or less, alternatively about 6.5 seconds or less, alternatively about 6.0 seconds or less, or alternatively about 6.0 seconds to about 7.0 seconds. For example, the cycle time of a high-speed thin-wall injection molding machine using high cavitation stacked molds (e.g., having 16 or more cavities) may be 7.0 seconds or less, or in the range of about 1 second to 7 seconds, or about 1 second, 2 seconds, 3 seconds, 4 seconds, 5 seconds, 6 seconds, or 7 seconds or any range in between.
[0075] Examples
[0076] The present invention will be described in more detail by specific examples. The examples described below are provided for illustrative purposes only and are not intended to limit the invention in any way. Those skilled in the art will readily recognize various insignificant variables that may be changed or modified to yield essentially the same result.
[0077] Example 1
[0078] (The effect of nucleating agents on molded products)
[0079] To evaluate the nucleating agent of the present invention (talc with an average particle size of 0.8 microns) and the control nucleating agent (talc with an average particle size in the range of 2 to 4 microns), TOTAL polypropylene 3727 was used, having an MFR of 20 g / 10 min (Fluff: 2.8), an XS% of 4, an XS range of 3.5 to 4.5, and a C2 content of 0.6 wt%.
[0080] Shrinkage measurements were performed on a 60x60x2mm plaque mold using a CNC (Computerized Numerical Control) microscope. The QV Apex 302 is a high-precision (1.5 micron accuracy) programmable microscope with a resolution of 0.1 micron. This instrument automatically and accurately measures shrinkage characteristics across the plaque. Figure 1 shows the effect of talc particle size on the warping of 3727. For TOTAL polypropylene 3727 nucleated with fine talc particle size, the difference in shrinkage between MD and TD (MD shrinkage - TD shrinkage) was nearly zero, which can be interpreted as a tendency for reduced warping of the injection-molded part. Figure 2 shows the effect of talc particle size on the shrinkage of 3727. Table 1 lists the shrinkage values. Table 2 lists the reduction in shrinkage of the nucleating agent of the present invention compared to the control nucleating agent. All of these data demonstrate that TOTAL polypropylene 3727 nucleated with fine active particle sizes exhibited a more homogeneous shrinkage rate in both longitudinal and transverse directions compared to larger active particle sizes. Figure 3 shows the effect of talc particle size on the measurement impact (Izod impact) of 3727. The measured impact properties were increased by 50% using the nucleating agent of the present invention compared to the control nucleating agent. Based on these results, it is believed that using a smaller talc particle size can result in better impact properties as well as more uniform shrinkage in all directions, and can significantly reduce warping of the end-use product without significant impact on other mechanical and optical properties.
[0081] 2-4 micrometer 0.8 micrometer unit shrinkage rate (Shrinkage) Bottom Left (MD) 1.446 1.379 % Bottom Left (TD) 1.383 1.436 % Large Center (MD) 1.393 1.346 % Large Center (TD) 1.304 1.349 % Small Center (MD) 1.731 1.669 % Small Center (TD) 1.575 1.648 % Top Right (MD) 1.304 1.39 % Top Right (TD) 1.513 1.442 % Bottom Left (Diff) -0.062 0.057 % Large Center (Diff) -0.0895 0.003 % Small Center (Diff) -0.157 -0.021 % Top Right (Diff) 0.209 0.052 %
[0082] Difference in shrinkage rate (Shrinkage difference) Reduction compared to 2-4 micrometer particles unit Bottom Left 8 % Large Center 97 % Small Center 87 % Top Right 75 %
[0083] Although embodiments of the present application and their advantages have been described in detail, it should be understood that various changes, substitutions, and modifications may be made in this specification without departing from the spirit and scope of the embodiments defined by the appended claims. Furthermore, the scope of the present application is not intended to be limited to specific embodiments of the processes, machines, manufacturing, compositions of materials, means, methods, and steps disclosed in the detailed description. Those skilled in the art will readily understand from the foregoing disclosures that there are currently existing or future-to-be-developed processes, machines, manufacturing, compositions of materials, means, methods, or steps that perform substantially the same function or achieve substantially the same results as the corresponding embodiments disclosed in this specification. Accordingly, the appended claims are intended to include such processes, machines, manufacturing, compositions of materials, means, methods, or steps within their scope.
Claims
Claim 1 A polymer composition comprising: a polyolefin polymer; and a nucleating agent having an average particle size of 0.001 micrometers (μm) or more and less than 2 μm; wherein the nucleating agent is present in an amount ranging from 100 ppm to 20,000 ppm, the nucleating agent is talc, and the isotropic shrinkage of the composition is in the range of 0% to 15%. Claim 2 delete Claim 3 A polymer composition according to claim 1, wherein the average particle size of the nucleating agent is in the range of 0.6 μm to 1.0 μm or 0.8 μm. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 A polymer composition according to claim 1, wherein the isotropic shrinkage rate of the composition is in the range of 0% to 5% or 0% to 1%. Claim 8 A polymer composition according to claim 1, wherein the composition comprises a polyolefin polymer identical to the polyolefin polymer and a nucleating agent identical to the nucleating agent, but has a differential shrinkage lower than the differential shrinkage of a control polymer composition in which the average particle size of the same nucleating agent is 2 μm or more. Claim 9 A polymer composition according to claim 1, wherein the composition comprises the same polymer as the polymer and the same nucleating agent as the nucleating agent, but has an increased Izod impact value in the range of 25% to 60% compared to a control polymer composition in which the average particle size of the same nucleating agent is 2 μm or more, said Izod impact value is measured by ASTM D-256-10. Claim 10 A polymer composition according to claim 9, wherein the Izod impact value is in the range of 20 ft·lb / in to less than 25.6 ft·lb / in. Claim 11 In claim 1, the polyolefin polymer comprises polypropylene, polyethylene, or both, forming a polymer composition. Claim 12 A polymer composition according to claim 1, wherein the polyolefin polymer comprises a homopolymer, a random copolymer, an impact copolymer, or any combination thereof. Claim 13 In claim 12, the homopolymer is a polymer composition comprising polypropylene and other C2-C8 alpha olefins in the range of 0% to 5% by weight. Claim 14 The polymer composition of claim 1, wherein the polyolefin polymer has a melt flow rate in the range of 1 g / 10 min to 200 g / 10 min measured according to ASTM D 1238 at a temperature of 230°C with a ram weight of 2.16 kg, a xylene solubles content of 3.5 to 4.5 weight%, or a combination thereof. Claim 15 A polymer composition according to claim 1, further comprising an additive, wherein the additive is an antioxidant, a neutralizing agent, an antistatic agent, a slip agent, a coloring agent, a mold release agent, a UV blocker, an oxidizing agent, a UV absorber, a fire retardant, a pigment, a dye, a filler, a flow modifier, or any combination thereof. Claim 16 A manufactured article comprising the polymer composition of claim 1. Claim 17 In claim 16, the manufactured article is a vehicle part, food container, cap, computer product, textile, pipe, film, bottle, non-food container, cup, lid, plate, tray, blister pack, or artificial turf. Claim 18 A method for manufacturing an article, comprising the step of molding the polymer composition of claim 1. Claim 19 A method for manufacturing an article according to claim 18, wherein the molding step comprises: injecting a fluid polymer composition into a mold; solidifying the polymer composition; and releasing the solidified composition from the mold, wherein the volume difference between the fluid polymer composition and the solidified composition is in the range of 0% to less than 20%. Claim 20 A method for manufacturing a manufactured article according to claim 19, wherein injection molding the polymer composition into the manufactured article comprises a cycle time in the range of 1 second to 10 seconds, or in the range of 1 second to 7 seconds, or in the range of 2 seconds to 7 seconds. Claim 21 A method for reducing warpage of a polyolefin polymer, wherein the method comprises the step of forming a polyolefin composition by adding a nucleating agent having an average particle size of 0.001 micrometers (μm) or more and less than 2 μm to the polyolefin polymer, wherein the nucleating agent is present in an amount ranging from 100 ppm to 20,000 ppm, the nucleating agent is talc, and the isotropic shrinkage rate of the composition is in the range of 0% to 15%. Claim 22 delete Claim 23 delete Claim 24 A method for reducing warping of a polyolefin polymer according to claim 21, wherein the polyolefin polymer comprises a homopolymer, a copolymer, or blends of polypropylene and polyethylene, or a combination thereof. Claim 25 A method for reducing warping of a polyolefin polymer according to claim 21, wherein the polyolefin composition comprises a polyolefin polymer identical to the polyolefin polymer and a nucleating agent identical to the nucleating agent, but has a differential shrinkage rate lower than that of a control polymer composition in which the average particle size of the same nucleating agent is 2 μm or more. Claim 26 delete Claim 27 A method for reducing warping of a polyolefin polymer, wherein, in either one of claims 21 and 24, the isotropic shrinkage rate of the composition is in the range of 0% to 5% or 0% to 1%.
Citation Information
Patent Citations
Automotive resin composition
JP1993295225A
Automotive article made from filler-containing tpo composition and method for making same
JP2008546891A
Polypropylene resin composition for hot water-pipes and panels
KR100648060B1
Polyolefin composition with excellent stiffness and impact strength
KR1019960001009A
Automotive articles prepared from filled TPO compositions, and methods of making the same
KR1020080041185A
